Existence and uniqueness of solution of inhomogeneous semilinear evolution equation with nonlocal condition - Tidke, Haribhau Laxman; More, R. T. (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In this paper, we study the existence and uniqueness of solution of inhomogeneous semilinear evolution equation with nonlocal condition in cone metric space. The result is obtained by using the some extensions of Banach's contraction principle in complete cone metric space.